Athletic identity and its relationship to moral values among physical education university students - L. M. Obeidat; H. I. Momani; T. T. Ammari; M. A. Rababah (Образование и наука)
Introduction. Physical education (PE) is one of the majors that some people and societies may consider less important than other majors which reduces the importance of the specialisation in this field. The investigation of athletic identity and its relationship to moral values among PE university students is an attempt to see the extent of the athletic identity may influence the possession of moral values among individuals who work in the PE field. This evaluation study seen from PE students’ perception is a new study that has not been carried out in Jordan. Most dominant researchers in Jordan and the Arab world evaluate athletic identity or possession of moral values but they have not studied the relation between the two variables.Aim. The present research aims to evaluate the athletic identity with relation to moral values based on the perceptions of PE university students.Methodology and research methods. A descriptive approach was used to analyse the data. To collect data, a questionnaire was applied. The questionnaire consists of two scales. The first is the Athletic Identity Measuremtent Scale (AIMS), consisting of 14 items distributed over three domains: socialisation identity (5 items), exclusivity (5 items), and negative emotion (4 items). The second is the Moral Values Scale (MVS), consisting of 27 items, distributed into five domains: responsibility (7 items), honesty, (5 items), socialisation (10 items), beauty (5 items), and competition (5 items). The study sample consisted of 280 students of Faculty of Physical Education at Yarmouk University.Results and scientific novelty. The results revealed that the level of athletic identity among students was rated high with statistically significant differences in favour of males. The domain of negative emotion was rated first, followed by exclusivity and socialisation identity respectively. The domains of moral values were estimated high in which competition domain was rated first, followed by beauty, honesty, responsibility and socialisation respectively. The results also demonstrated that there was a positive statistically significant relationship between athletic identity and moral values.Practical significance. The study recommends consolidating athletic identity among students through increasing sports participation and activities, strengthening academic courses that deal with sports culture and sports values, involving female students in sports activities to enhance the level of their athletic identity to bridge the gap in the level of athletic identity between them and male students.